Nursing students' perceptions of caring for dying people, after one year in nursing school. (June 2016) - Österlind, Jane; Prahl, Charlotte; Westin, Lars; Strang, Susann; Bergh, Ingrid; Henoch, Ingela; Hammarlund, Kina; Ek, Kristina
Abstract: Aim: To describe Swedish nursing students' perceptions of caring for dying people after the first year of a three year in a nursing programme at three university nursing schools in Sweden. Methods: Interviews (n = 17) were undertaken with nursing students at the end of their first year. A phenomenographic approach was used to design and structure the analysis of the nursing students' perceptions. Results: The analysis resulted in five categories: 1) from abstract to reality, 2) from scary to natural, 3) increased knowledge can give bad conscience, 4) time limits versus fear of end-of-life conversations, and 5) meeting with relatives. Conclusion: Nursing students need to be prepared both theoretically and within practice to encounter death and dying and to care for dying persons. By combining their theoretical knowledge of dying and death with their own encounters of death and dying people in practice, the students can be supported to develop an understanding of dying and death as a natural part of life rather than something frightening. Highlights: The students perceive that they are spectators when faced with a dying person Death is described as something abstract, that, over time, becomes more real The perceptions change from see a dying person as an object to be seen as a subject